Obama and the biracial factor : the battle for a new American majority. - Jolivétte, Andrew, 1975- (Policy Press, 2012)
Obama and the Biracial Factor is the first book to explore the significance of mixed-race identity as a key factor in the election of President Obama and examines the sociological and political relationship between race, power, and public policy in the United States.